Rare atypical type a thymoma: a case report and literature review - Liling Qin; Fanrong Wang; Liqiao Chen; Tao Li; Gang Wang; Ning Zhou (BMC, 2024)
Abstract Background An atypical type A thymoma variant was recently added to the World Health Organization classification of type A thymoma in 2015. This novel form of type A thymoma presents with hypercellularity, increased mitotic activity, and necrosis. In particular, necrosis seems to be related to postoperative recurrence and metastasis, but the clinical significance of these changes still needs to be studied. Case presentation A 76-year-old man underwent thoracoscopic surgery for tumour resection due to an anterior mediastinal mass. Pathological examination revealed that the tumour invaded the surrounding thymic tissue. Cells were arranged in nest-like and whirl-like patterns, accompanied by prominent comedo-like necrosis, increased cell density, mild atypia, and a mitotic count of 4-6 per 10 high-power fields. Immunohistochemistry revealed positive expression of cytokeratin 19 and P63 in the tumour cells. Lymphocytes in the background were positive for CD3 and CD5, did not express terminal deoxynucleotide transferase, CD20, or CD117, and had an MIB-1 labelling index(LI) value of 15%. On the basis of these findings, the tumour was finally diagnosed as an atypical type A thymoma variant. Conclusions We report a case of atypical type A thymoma and review the literature to enhance our understanding of and provide accumulated pathological data on this rare disease.